The factors related to exclusive breastfeeding in mother of baby ages 6 - 24 months - dea dwi ayu ningrum; Miftahul Jannah (ARGIPA (Arsip Gizi dan Pangan), 2019)
Breastfeeding has a dynamic composition and it is suitable for the baby's needs so that ASI is the optimal nutrition for babies. Breast milk should be given to children for at least six months to reduce morbidity and mortality. However, exclusive breastfeeding coverage in Babakangebang village is still low and far from target achievement. The purpose of this study was to determine the factors related to exclusive breastfeeding practices for infants 6-24 months in Babakangebang Village, Cirebon. The research used a case-control study conducted on the subjects with the number of 32 as the case and 32 as the control. Data collected through questionnaires by direct interview method. The chi-square test was used to analyze the relationship between dependent and independent variables. The results showed that factors related to exclusive breastfeeding practices were family support with OR 3,857 and husbands' support with OR 2,778. The other factors studied, such as maternal education, practice of early breastfeeding initiation, maternal knowledge, as well as the support of health workers, had no relationship with exclusive breastfeeding practices. Keywords: Exclusive Breastfeeding, Supporting, Education, Knowledge, Early Breastfeeding Initiation